Interleukin 35 is an independent prognostic factor and a therapeutic target for nasopharyngeal carcinoma - Zhang, Yongquan; Sun, Hong; Wu, Hui; Tan, Qindong; Xiang, Kai (Contemporary Oncology/Współczesna Onkologia, 2015)
Aim of the study: Interleukin (IL)-35 is composed of two subunits: Epstein-Barr virus-induced gene 3 (EBI3) and IL-12p35. Recently, overexpression of IL-35 has been found in several types of cancers. However, its clinical significance in nasopharyngeal carcinoma is still obscure. We have studied the clinical significance of IL-35 expression and its correlation with outcome of nasopharyngeal carcinoma patients. Material and methods: Interleukin 35 expression was investigated in 80 nasopharyngeal carcinoma cases by immunohistochemistry. Moreover, Fisher’s exact test, Kaplan-Meier plots, and Cox proportional hazards regression were utilized to analyse these results. Results : In the present study, IL-35 is highly expressed in the majority of nasopharyngeal carcinoma samples. EBI3 and p35 immunoreactivity in nasopharyngeal carcinoma samples was 67.5% and 51.3%, respectively. Both EBI3 and p35 expressions were significantly associated with advancement of tumour stage. In addition, EBI3 expression was also correlated with lymph node metastasis. Further analysis showed that EBI3 or p35 staining indicated unfavourable prognosis (p < 0.05). Multivariate analysis suggested EBI3 was an independent prognostic predictor (p < 0.05). Conclusions : Our results indicate for the first time that IL-35 is correlated with progression of nasopharyngeal carcinoma. Therefore, IL-35 may be a useful target for the treatment of nasopharyngeal carcinoma.